2012
DOI: 10.1007/s11743-012-1371-y
|View full text |Cite
|
Sign up to set email alerts
|

Synergism and Performance Optimization in Liquid Detergents Containing Binary Mixtures of Anionic–Nonionic, and Anionic–Cationic Surfactants

Abstract: In this paper evaluation of surface active and application properties in liquid detergent formulations containing binary mixtures of anionic–nonionic, and anionic–cationic surfactants is discussed. Surfactants used include: linear alkylbenzene sulfonate (LAS), alcohol ether sulfate (AES‐2EO), alcohol ethoxylate (AE‐7EO), lauryl dimethyl amine oxide, and alkyl hydroxyethyl dimethyl ammonium chloride (AHDAC). Surface active parameters relating to the effectiveness and efficiency of surface tension reduction were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…2. It can be seen that mixture of these anionic surfactants showed synergism in detergency performance compared to using a single surfactant which is consistent with the literature [40]. More than 90 % canola oil detergency efficiency could be achieved using surfactant mixtures as compared to 68 % using SDOSS alone or 85 % using C 10 -18PO-2EO-NaSO 4 alone.…”
Section: Detergencysupporting
confidence: 87%
“…2. It can be seen that mixture of these anionic surfactants showed synergism in detergency performance compared to using a single surfactant which is consistent with the literature [40]. More than 90 % canola oil detergency efficiency could be achieved using surfactant mixtures as compared to 68 % using SDOSS alone or 85 % using C 10 -18PO-2EO-NaSO 4 alone.…”
Section: Detergencysupporting
confidence: 87%
“…As shown in Table 9, the results of detergency of PFAD-AR liquid detergent formulations were comparable with those of CLD and PO-AR-based liquid detergent formulations at 0.1, 0.25 and 0.5% concentration. LD 5 and LD 4 show better percentage detergency as compared to LD 1 , LD 2 , LD 3 and LD 6 of PFAD-AR-based liquid detergent formulations. In this study, presence of alkyd resin along with SLS/SLES not only enhances the cleaning power but also increases the efficiency of detergents which helps in soil removal.…”
Section: Detergencymentioning
confidence: 92%
“…Surfactant mixture systems include the mixtures of the same types of surfactant compositions and different types of surfactant compositions (Jadidi et al, ; Zhang et al, ; Zheng et al, ). The former surfactant mixtures can be divided into cationic/cationic mixture (Patel et al, ), anionic/anionic mixtures (Szymczyk and Jańczuk, ), and nonionic/nonionic mixtures (Szymczyk and Jańczuk, ), while the latter ones mainly consist of cationic/nonionic mixtures (Fatma et al, ), anionic/nonionic mixtures (Tucker et al, ), anionic/zwitterionic mixtures (Maneedaeng and Flood, ), anionic‐nonionic/nonionic mixtures (Liu et al, ), and anionic/cationic mixtures (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Surfactant mixture systems include the mixtures of the same types of surfactant compositions and different types of surfactant compositions (Jadidi et al, 2013; Supporting information Additional supporting information may be found online in the Supporting Information section at the end of the article. 1999; Zheng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%